Learners’ Perceptions for Teacher’s Feedback of Their Oral Performances: Case Study - Karima Fajarwati; Ahmad Munir; Tengsoe Tjahjono (Institut Agama Islam Negeri Palopo, 2021)
The feedbacks given by teacher is the important role in monitoring learners during the learning process. Teacher serves feedbacks in various ways, can be correction, praise, suggestion, and so on. By receiving feedbacks, learners are able to realize their errors and they feel motivated to develop and improve their performance. However, not all learners have the same characteristics in accepting the feedbacks well. Some of learners may feel insecure during or after getting feedbacks. Therefore, this study explores learners’ perceptions for teacher’s feedback of their oral performances, whether they feel motivated or feel the other way. The questionnaires were the main tool to gain the information from the learners, and followed by the interview from some learners to get the further and detail explanation. The result shows that most of learners feel motivated from the teacher’s feedbacks, and they have intention to perform better because they understand their errors. However, there are some other aspects that decrease their motivation by the way teacher delivers the feedbacks.